ANALISIS FRAMING BERITA PENERTIBAN MINIMARKET ILEGAL PADA SURAT KABAR POS KOTA DAN INDOPOS - Rizky, Muhammad (WACANA: Jurnal Ilmiah Ilmu Komunikasi, 2012)
Pos Kota newspaper and Indopos, has a method of storytelling (story telling), respectively in reporting illegal demolition in Jakarta minimarket. Pos Kota newspaper leads to a more traditional market increasingly cornered by many minimarket. While Indopos understand correctly that the superior position minimarket, but wherever possible, non-partisan one. This study uses the social construction of reality from Peter L. Berger and Thomas Luckman. The method used is a framing analysis developed by Pan and Gerald M. Zhongdang Kosicki. From the research findings, Pos Kota looks alignments against traditional traders can be seen from the syntactic and rhetorical elements. While Indopos more directed to the syntactic elements.